EFEKTIVITAS PENGAWASAN IZIN PENYIARAN TV KABEL BERLANGGANAN OLEH KOMISI PENYIARAN INDONESIA DAERAH (KPID) RIAU DI KOTA PEKANBARU - Indra Mugiono; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Indra Mugiono, NIM 1001134918, Monitoring the effectiveness of the Broadcasting License Subscribe Cable Tv By the Regional Indonesian Broadcasting Commission Riau in Pekanbaru, supervisor : Dr. Harapan Tua R.F.S, M.SiCable TV channels network presence began in the spotlight Dishubkominfo Pekanbaru. Based on data Dishubkominfo none of the cable TV network in Pekanbaru permit the implementation of the cord. Meanwhile Transportation Department officials also met officials technicians were installing cables cable TV networks that do not have an operating license for its cable. Illegal practices immediately rose stopped a team of officers. The development of cable TV in Pekanbaru very rapidly this time we can read in the press that the proliferation of cable TV company in Pekanbaru, with so much needed oversight conducted by the Indonesian Broadcasting Commission of Riau.The theory used as the analysis in this study is Handayanigrat (2005; 32) said that effective supervision can help businesses to organize work in order to conform with the plans related to the problem Effectiveness Monitoring Permits Broadcasting Cable TV Subscription By Regional Indonesian Broadcasting Commission (Commission) Riau in the city of Pekanbaru.The results of this study indicate, Effectiveness Monitoring Cable TV Broadcasting License Subscription by the Indonesian Broadcasting Commission of Riau in Pekanbaru City should be supervised broadcasting license. However, in practice there are still many who do not have cable TV broadcasting license by broadcasting commission Riau. And the factors that influence is a change in the organization, their problems in Riau regional broadcast Commission with regard to the role of independent organizations under the Act, decentralization of power relating to broadcasting legislationKeywords : Effectiveness of Supervision, Cable TV Subscription.